Role Overload, Self- Efficacy, Locus of Control and Job Performance among Employees of a Printing Company in Malaysia - Omar, Muhamad Khalil; Hussein, Norashikin; Azli, Norazamimah (Information Management and Business Review, 2016)
Abstract: Job performance becomes the most commonly discussed issue in the recent years even though many research have been conducted. As the employee is the most important asset for an organization, various factors influencing the employee performance need to be ascertained. For companies that offer services to customers, their employees’ job performance could impact the loyalty of the customers and longevity of the business. However, constant dealing with high and various consumer demands, employees of printing company could easily be stressful hence requiring them to control their emotions. Therefore this study investigated the effects of role overload, self-efficacy, and locus of control towards employee job performance. A total of 67 employees of a small printing company located in Klang Valley, Malaysia had participated in the survey of this descriptive and correlational study. The results indicated that there was a strong positive relationship between self-efficacy and job performance, the meanwhile locus of control had a moderate positive relationship with job performance. This study contributes to the body of knowledge by validating the positive association of both self-efficacy and locus of control with employee job performance. The practitioners could also make reference to this study in order to properly manage the performance of their employees.